Korelasi Antara Kadar Vitamin C dengan Kadar Methemoglobin Darah Lansia di Kecamatan Pakem Kabupaten Sleman - Prasetyastuti Prasetyastuti (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Oxidative damage by free radical can cause aging process. Erythrocyte as an oxygen – carrying agent has high risk of oxidative injury which can inducemethemoglobin production. Vitamin C is an exogen antioxidant that work in aqueous phase like blood and can react with free radical before they initiate the oxidative injury.Objectives: The aim of this study was to find out whether there is possibility of correlation between vitamin C and methemoglobin level in blood of elderly living in Pakem DistrictMethod: This was an observational research with cross sectional design, in which 32 elderly from Pakem District were subjects. The blood sample was taken from cubital vein. Determination of vitamin C and methemoglobin level used spectrophotometer. Pearson Correlation was employed to analyze the data.Results: The vitamin C and methemoglobin level of the elderly 0,43 + 0,25 mg/dl and 0,035 + 0.02% respectively. The correlation between vitamin C and methemoglobin level was not significant ( p = 0.771).Conclusion: The vitamin C was not correlated with the methemoglobin level.Keywords: vitamin C, methemoglobin, elderly, free radica